Phylogenetic analysis of full‐length, early infection, hepatitis C virus genomes among people with intravenous drug use: the InC3 Study. Issue 1 (3rd November 2016) - Rodrigo, C.; Eltahla, A. A.; Bull, R. A.; Luciani, F.; Grebely, J.; Dore, G. J.; Applegate, T.; Page, K.; Bruneau, J.; Morris, M. D.; Cox, A. L.; Osburn, W.; et al.
Summary: Cross‐continental phylogenetic analysis is important to understand subtle molecular differences of currently circulating hepatitis C virus (HCV) subtypes. Existence of such differences can be crucial in pursuing a universal hepatitis C vaccine. We characterized molecular epidemiology of early HCV infections identified across nine cohorts [North America (n=4), Australia (n=4) and Europe (n=1)] in the International Collaborative of Incident HIV and Hepatitis C in Injecting Cohorts (InC 3 ). One hundred and ninety‐two full‐length HCV genomes were amplified from plasma of incident infections and subjected to next generation sequencing to establish the largest cross‐continental, full‐length acute HCV genomic data set available to date. Genomes from the most common subtypes (1a: n=94, 2b: n=15 and 3a: n=68) were used in phylogenetic analysis. Using full genome trees, 78 sequences (44%) were found to lie within 29 phylogenetic clusters/pairs defined on the basis of molecular similarity of consensus sequences. Of these, 26 each had exclusively Australian or North American sequences indicating a strong geographical bias for molecular similarity. On further analysis of behavioural and demographic associations, binary logistic regression analysis showed that older age and non‐Caucasian ethnicity were significantly associated with clustering. HCV probably evolves in micro‐epidemics within geographically isolated communities.